2017
DOI: 10.1073/pnas.1613254114
|View full text |Cite
|
Sign up to set email alerts
|

C-type lectin receptor DCIR modulates immunity to tuberculosis by sustaining type I interferon signaling in dendritic cells

Abstract: Immune response against pathogens is a tightly regulated process that must ensure microbial control while preserving integrity of the infected organs. Tuberculosis (TB) is a paramount example of a chronic infection in which antimicrobial immunity is protective in the vast majority of infected individuals but can become detrimental if not finely tuned. Here, we report that C-type lectin dendritic cell (DC) immunoreceptor (DCIR), a key component in DC homeostasis, is required to modulate lung inflammation and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 47 publications
(44 reference statements)
2
71
0
Order By: Relevance
“…Authors proposed that as prolonged type-I IFN signaling during chronic virus infection facilitates virus persistence by inducing negative immune regulators, CLEC12A inhibition may be clinically beneficial in cases of persistent infection (116,117). Similarly, the inhibitory receptor DCIR was shown to sustain type-I IFN signaling in DCs through interaction with an unidentified endogenous ligand(s) (118). Although both of these CLRs contain an ITIM in their cytoplasmic tail, and are thought to act as negative regulators of immune cell signaling, these results suggest that ITIM can somehow activate, rather than inhibit, some signaling pathways (22,118).…”
Section: Clec12a (Micl Dcal2 Cll-1 or Cd371)mentioning
confidence: 99%
See 1 more Smart Citation
“…Authors proposed that as prolonged type-I IFN signaling during chronic virus infection facilitates virus persistence by inducing negative immune regulators, CLEC12A inhibition may be clinically beneficial in cases of persistent infection (116,117). Similarly, the inhibitory receptor DCIR was shown to sustain type-I IFN signaling in DCs through interaction with an unidentified endogenous ligand(s) (118). Although both of these CLRs contain an ITIM in their cytoplasmic tail, and are thought to act as negative regulators of immune cell signaling, these results suggest that ITIM can somehow activate, rather than inhibit, some signaling pathways (22,118).…”
Section: Clec12a (Micl Dcal2 Cll-1 or Cd371)mentioning
confidence: 99%
“…Similarly, the inhibitory receptor DCIR was shown to sustain type-I IFN signaling in DCs through interaction with an unidentified endogenous ligand(s) (118). Although both of these CLRs contain an ITIM in their cytoplasmic tail, and are thought to act as negative regulators of immune cell signaling, these results suggest that ITIM can somehow activate, rather than inhibit, some signaling pathways (22,118). Whether these receptors deliver a signal on their own through the ITIM motif or require a co-receptor will need further molecular dissection.…”
Section: Clec12a (Micl Dcal2 Cll-1 or Cd371)mentioning
confidence: 99%
“…The original member of this family, Clec4a2, the likely ortholog of the single CLEC4A gene in humans, encodes a lectin with a broad binding specificity for mannose and fucose [112]. Studies on knockout mice lacking Clec4a2 continue to be based upon the claim that the lectin is mainly expressed by DC [113] but the global analysis showed that it is more highly-expressed in most isolated macrophage populations. Two of the DC-associated clusters contained other members of the family, Clec4a4 and Clec4b2.…”
Section: Dendritic Cell Co-expression Clustersmentioning
confidence: 99%
“…Clec4a encodes DCIR, a C-type lectin receptor and member of the dendritic cell immunoreceptor (DCIR) family that was first described as an attachment factor for human immunodeficiency virus (HIV)-1 in DC (96). DCIR has also been reported to potentiate DC cross-presentation of antigen to CD8 T cells (97) and sustain type I IFN signaling (98). Notably, a polymorphism in DCIR, SNP rs2377422, is a genetic susceptibility factor for SLE and Sjogren’s syndrome (99), two autoimmune diseases where excessive apoptosis and impaired apoptotic cell clearance contribute to disease pathogenesis (15, 100).…”
Section: Suppression Of Inflammation and Immune Response By Apoptoticmentioning
confidence: 99%
“…97 DCIR has also been reported to potentiate DC cross-presentation of antigen to CD8 T cells 98 and sustain type I IFN signaling. 99 Notably, a polymorphism in DCIR, SNP rs2377422, is a genetic susceptibility factor for SLE and Sjogren's syndrome, 100 two autoimmune diseases where excessive apoptosis and impaired apoptotic cell clearance contribute to disease pathogenesis. 15,101 Clec4b1 encodes DCAR, a different member of the DCIR family that delivers antigens to the endocytic pathway in DC and enhances antigen-specific T-cell responses.…”
Section: Subset-specific Pathways Of Suppressing Inflammationmentioning
confidence: 99%